Implementation of Multi-Room Computer Laboratory Network Infrastructure Based on Star Topology in an Educational Environment - Andi Zulherry; Al-Khowarizmi (Ilmu Bersama Center, 2026)
Reliable network infrastructure is essential to support digital-based learning activities in educational institutions, particularly in computer laboratories that require stable and simultaneous internet access for a large number of devices. This study aims to implement a multi-room computer laboratory network infrastructure consisting of 160 PCs distributed across four laboratory rooms, each containing 40 computers. The network architecture is designed using a star topology, where each PC connects to an access switch within its respective room, and all switches are connected to a central modem acting as the primary gateway and Dynamic Host Configuration Protocol (DHCP) server. The infrastructure follows a peer-to-peer model without centralized server deployment or bandwidth management configuration. The implementation process includes physical network installation, structured cabling, automatic IP configuration through DHCP, and connectivity testing to ensure proper communication and internet accessibility. The results show that all 160 PCs successfully obtained IP addresses without conflicts and were able to access the internet simultaneously under normal operating conditions. The star topology provided ease of installation, simplified troubleshooting, and effective fault isolation. These findings indicate that the implemented infrastructure operates reliably as a foundational network system and provides a baseline for future development, including network segmentation, bandwidth management, and centralized service integration.